2010
DOI: 10.1590/s0103-64402010000200012
|View full text |Cite
|
Sign up to set email alerts
|

The recurrence of leprosy reactional episodes could be associated with oral chronic infections and expression of serum IL-1, TNF-α, IL-6, IFN-γ and IL-10

Abstract: The aim of this study was to determine whether the presence of leprosy reactional episodes could be associated with chronic oral infection. Thirty-eight leprosy patients were selected and divided into 2 groups: group I - 19 leprosy patients with oral infections, and group II - 19 leprosy patients without oral infections. Ten patients without leprosy, but presenting oral infections, were assigned to the control group. Leprosy patients were classified according to Ridley and Jopling classification and reactional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 15 publications
(15 reference statements)
3
35
0
3
Order By: Relevance
“…The mechanism of an "early/transient" Th2 response leading to chronic inflammation is likely involved not only in ABPM but also in other persistent infections. The chronic presence of microbe and absence of clearance are frequently associated with a perturbed immune response characterized by a mixed cytokine profile rather than with a "pure" Th2 immunity (3,8,19,29,38). Our data from the IL-4…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of an "early/transient" Th2 response leading to chronic inflammation is likely involved not only in ABPM but also in other persistent infections. The chronic presence of microbe and absence of clearance are frequently associated with a perturbed immune response characterized by a mixed cytokine profile rather than with a "pure" Th2 immunity (3,8,19,29,38). Our data from the IL-4…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that PBMCs present different levels of proliferation index of cytokines when they are stimulated in vitro with Mycobacterium leprae extracts [21][22][23] . On the other hand, we observed that the leprosy reactional episodes are frequent in patients presenting oral infections 14,15 and other coinfections 24 . Therefore, this study attempted to clarify whether chronic oral infections could influence the intracellular production of cytokines in leprosy patients, and to verify the relationship with the development of reactional episodes.…”
Section: A B C D Discussionmentioning
confidence: 72%
“…The coexistence of oral chronic infections with leprosy can modulate the inflammatory reaction by elevation of the intracellular inflammatory markers expression, probably stimulating a spill-over of these inflammatory products into the peripheral circulation where they can act as inducers of an inflammatory reaction, exacerbating the insidious chronic evolution of leprosy and, consequently, acting like an inducer, stimulatory or maintaining factor in leprosy reactions 14,15,24 . In addition, the presence of these chronic infections can influence the production of intracellular cytokines, and can reflect the fact that most of the leprosy patients with coinfection (Group I) presented reactional episodes, corroborating the hypothesis of a synergistic action of the two kinds of inflammatory reaction on the course of leprosy.…”
Section: A B C D Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we evaluated the expression of proinflammatory serum biomarkers in LPs presenting oral infections (periodontal diseases, irreversible pulpitis, pulpal necrosis, or inflammatory periapical lesions) and we observed higher CRP, IL-10, IL-1 and IL-6 levels in the presence of oral infections, suggesting that oral infections can act as a maintenance factor of the proinflammatory state (Motta et al 2010. Thus, the coexistence of chronic oral infections with leprosy can stimulate the inflammatory reaction by elevating the expression of intracellular inflammatory markers.…”
Section: Endocrine Axis In Leprosy -mentioning
confidence: 96%